2014
DOI: 10.1038/mi.2013.53
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy-specific glycoprotein 1 (PSG1) activates TGF-β and prevents dextran sodium sulfate (DSS)-induced colitis in mice

Abstract: Transforming growth factor beta (TGF-βs) are secreted from cells as latent complexes and the activity of TGF-βs is controlled predominantly through activation of these complexes. Tolerance to the fetal allograft is essential for pregnancy success; TGF-β1 and -β2 play important roles in regulating these processes. Pregnancy-specific β-glycoproteins (PSGs) are present in the maternal circulation at high concentration throughout pregnancy and have been proposed to have anti-inflammatory functions. We found that r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
78
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(91 citation statements)
references
References 47 publications
9
78
0
4
Order By: Relevance
“…Administration of PSG1 protected mice from dextran sulfate induced colitis and the observed protective effect of PSG1 was inhibited by co-administration of a neutralizing anti-TGF-b antibody (Blois et al, 2013). PSG1-treated mice expressed lower levels of the pro-inflammatory cytokines TNF-a and IFN-g compared to protein control-treated mice.…”
Section: Pregnancy-specific Glycoproteins 277mentioning
confidence: 98%
See 2 more Smart Citations
“…Administration of PSG1 protected mice from dextran sulfate induced colitis and the observed protective effect of PSG1 was inhibited by co-administration of a neutralizing anti-TGF-b antibody (Blois et al, 2013). PSG1-treated mice expressed lower levels of the pro-inflammatory cytokines TNF-a and IFN-g compared to protein control-treated mice.…”
Section: Pregnancy-specific Glycoproteins 277mentioning
confidence: 98%
“…An experimental approach employing a cell-free system indicated that PSG1 is able to activate the small latent complex (SLC) of TGF-b1 in a dose-dependent manner (Blois et al, 2013). Because the small latent form of TGF-b2 is not commercially available, reporter assays were used and strongly suggested that PSG1 can also activate this isoform (Blois et al, 2013). Whether PSG1 can activate the latent TGF-b3 isoform remains to be investigated.…”
Section: Pregnancy-specific Glycoproteins 277mentioning
confidence: 99%
See 1 more Smart Citation
“…Three large gene families (prolactins, ceacams, and pregnancy-specific glycoproteins) have increased in number across placental mammalian evolution and are expressed in the placenta and hypothalamus. The pregnancyspecific glycoproteins (Psgs) are members of the Ig superfamily and induce the release of anti-inflammatory cytokines (30). These glycoproteins are thought to be important for modulating the innate and adaptive immune response to assure a successful pregnancy (31).…”
Section: Genetic Stability and Variancementioning
confidence: 99%
“…Human and mouse PSGs induce Th2 cytokine production in human and mouse monocytic and other cells (Wessells et al 2000, Snyder et al 2001, Motrán et al 2002, Waterhouse et al 2002, Ellerman et al 2003, Ha et al 2005, Blois et al 2012, Martínez et al 2012, and human PSG1 activates TGFb1 in a cell-free system and reduces inflammation in a mouse colitis model (Blois et al 2014). Human and mouse PSGs induce tube formation by endothelial cells in matrigel, suggesting that PSGs may be pro-angiogenic in vivo (Lisboa et al 2011, Blois et al 2012.…”
Section: Introductionmentioning
confidence: 99%